Pendampingan Pendaftaran Nomor Induk Berusaha (NIB) pada UMKM Brownis D’Morena Kelurahan Gununganyar - Bayu, M Rizky Bayu Pratama; Wikartika, Ira (Universitas Negeri Surabaya, 2024)
Micro, small and medium enterprises or MSMEs are a category of businesses that cover a small to medium scale in terms of production, turnover or labor. MSMEs are the backbone that supports the development of the country's economy. MSMEs are one of the factors that generate the economy by providing their own jobs, so that they can reduce unemployment and poverty in Indonesia. However, one of the factors that must be considered when establishing a business is business legality, MSME actors must be officially registered with the government and have a business license, the type of business legality that must at least be owned is a Business Identification Number certificate, NIB registration itself can be done through the Online Single website. By having a Business Identification Number Certificate, the business has been officially registered with the government. The benefits of having a Business Identification Number are obtaining legal protection and facilitating access to finance because many financial institutions make NIB a requirement for applying for capital loans. Therefore, UPN veteran East Java students who take part in the Bina Desa program in Gununganyar Village, Surabaya have the initiative to provide assistance and socialization to MSMEs in Gununganyar Village, one of which is the D'morena Brownies business to obtain an NIB certificate with the aim of improving the welfare of MSMEs.